PENGARUH PROFITABILITAS, CASH POSITION , LEVERAGE , DAN GROWTH TERHADAP KEBIJAKAN DEVIDEN - Ishaq, Alfina Febrisa (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to analyze the profitability, cash position, leverage, and growth in a company to the dividend policy of a company. The result of this research shows that the profitability does not have any influence to the dividend policy since the company has commitment to share the dividend regularly and it is not influenced by the amount of the profit which has been obtained. The company will use retained earnings to be invested in productive sectors in order to gain large benefits and to strengthen the capital of the company for the following years. Cash position does not have any influence to the dividend policy because of the presence of other instruments i.e. inventory and account receivables. Leverage in this matters is debt to equity ratio has negative influence to the dividend share policy, it means that when the value of leverage of a company is getting high, the number of dividend that will be shared by the company is getting small. Growth in this case is asset growth does not have any influence to the company dividend share policy it. Keywords: Dividend Policy, Profitability, Cash Position, and Growth